Β-(Methoxy-(substitutedphenyl)-methyl)-γ-butyrolactones: A short synthesis from cinnamyl acetate. Issue 4 (16th February 2016) - Singh, Buddh; Sharma, Shiromani; Taneja, Subhash C.; Shankar, Ravi; Sangwan, Payare L.
ABSTRACT: A simple and short synthesis has been revealed for the preparation of (±) β-(Methoxy-(substitutedphenyl)-methyl)-γ-butyrolactones. The reaction of cinnamyl acetate with Mn(OAc)3 · 2H2 O in boiling acetic acid containing acetic anhydride gave the products2 and3, which further cyclized in 3% H2 SO4 /CH3 OH to afford the butyrolactones (8a–e ), which are intermediates of lignin, in good to moderate yields. GRAPHICAL ABSTRACT: